2001
DOI: 10.1046/j.1365-2044.2001.01918-9.x
|View full text |Cite
|
Sign up to set email alerts
|

Herniation of tracheal tube cuffs: a simple teaching model

Abstract: Letters (two copies) must be typewritten on one side of the paper only and double spaced with wide margins. Copy should be prepared in the usual style and format of the Correspondence section. Authors must follow the advice about references and other matters contained in the Notice to Contributors to Anaesthesia printed at the back of each issue. The degree and diplomas of each author must be given in a covering letter personally signed by all the authors. Correspondence presented in any other style or format … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Kao et al [38] reported hyperinflation of ETT cuff resulting in the herniation of the cuff balloon in front of the tube's end, potentially blocking gas exchange during the creation of tracheal stoma. Wright and Baruch [39] observed a situation where there was a leak due to the herniation of large-volume and low-pressure cuffed ETT when more and more air was injected into the cuff. In this situation, the cuff herniated upwards through the glottis.…”
Section: Problem Associated With Over-inflation Of Intracuff Pressurementioning
confidence: 99%
“…Kao et al [38] reported hyperinflation of ETT cuff resulting in the herniation of the cuff balloon in front of the tube's end, potentially blocking gas exchange during the creation of tracheal stoma. Wright and Baruch [39] observed a situation where there was a leak due to the herniation of large-volume and low-pressure cuffed ETT when more and more air was injected into the cuff. In this situation, the cuff herniated upwards through the glottis.…”
Section: Problem Associated With Over-inflation Of Intracuff Pressurementioning
confidence: 99%
“…Physiologically, blood flow to the antero-lateral part of the trachea has been reported to be compromised at pressures exceeding 30 cmH 2 O and become obstructed at pressures exceeding 50 cmH 2 O 21 . Previous studies have also shown that hyperinflation of ETT cuff could result in the herniation of the cuff balloon in front of the tube’s end 22 or upwards through the glottis 23 , thereby jeopardizing gas exchange. Hence, general practice guidelines recommended a cuff inflation pressure below 30 cmH 2 O (22 mmHg) 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The cause for this can be displacement of the tube or overinflation of ETT cuff. [ 1 ] Usually, it is noticed by the sound of gas leaking around the tube or when there is a fall in tidal volume and end-tidal carbon dioxide (CO 2 ). Confirmation and repositioning of the ETT require direct laryngoscopy which has disadvantages such as stress response[ 2 ] and is difficult to perform intra-operatively, particularly if the patient is not in supine position.…”
Section: Introductionmentioning
confidence: 99%